The identification of post-starburst galaxies at z∼1 using multiwavelength photometry: a spectroscopic verification - Maltby, David T.; Almaini, Omar; Wild, Vivienne; Hatch, Nina A.; Hartley, William G.; Simpson, Chris; McLure, Ross J.; Dunlop, James; Rowlands, Kate; Cirasuolo, Michele (Oxford University Press, 2016)
Despite decades of study, we still do not fully understand why some massive galaxies abruptly switch off their star formation in the early Universe, and what causes their rapid transition to the red sequence. Post-starburst galaxies provide a rare opportunity to study this transition phase, but few have currently been spectroscopically identified at high redshift (z > 1). In this paper, we present the spectroscopic verification of a new photometric technique to identify post-starbursts in high-redshift surveys. The method classifies the broad-band optical–nearinfrared spectral energy distributions (SEDs) of galaxies using three spectral shape parameters (supercolours), derived from a principal component analysis of model SEDs. When applied to the multiwavelength photometric data in the UKIDSS Ultra Deep Survey, this technique identified over 900 candidate post-starbursts at redshifts 0.5<z<2.0. In this study, we present deep optical spectroscopy for a subset of these galaxies, in order to confirm their post-starburst nature. Where a spectroscopic assessment was possible, we find the majority (19/24 galaxies; ∼80 per cent) exhibit the strong Balmer absorption (H δ equivalent width Wλ > 5 angstrem) and Balmer break, characteristic of post-starburst galaxies.We conclude that photometric methods can be used to select large samples of recently-quenched galaxies in the distant Universe.